PENGARUH KERAGAMAN PRODUK, HARGA, DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA SWALAYAN SINAR HARAPAN DI KABUPATEN SITUBONDO - Dwi Perwitasari Wiryaningtiyas; Karnadi Karnadi; Azimatul Umami (Growth, 2020)
This study aims to (1) to determine the effect of product diversity, price, and location partially influences customer satisfaction (2) to find out the effect of product diversity, price, and location simultaneously affect customer satisfaction (3 to find out among the diversity of products, prices, and locations that are the most dominant influence on customer satisfaction. The method used is quantitative. The results of the study are multiple linear regression equation Y = -1,711E-16 + 0.046X1 + 0.293X2 + 0.212X3 + e. partially the diversity of the product has no significant effect with the value of tcount smaller than ttable (0.430) <(1,985) or sig a 0.668> 0.05, the price of partial effect shows the value of tcount is greater than ttable (2,284)> (1,985) or sig a 0,000 <0.05, the location has no partial effect by showing the tcount value smaller than ttable (1,930) <(1,985) or sig a 0.057> 0.05. Simultaneously the diversity of products, prices, and location affect customer satisfaction with a calculated Fcount of 8.015 values greater than the Ftable of 2.70 or Fcount of 8.015> Ftable of 2.70. The variable with the most dominant influence in this study is the price with a value of 2,824.